2003
DOI: 10.1002/poc.605
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the π‐electron delocalization in exocyclically substituted heptafulvene derivatives

Abstract: Eleven mono-and eight di-exocyclically substituted heptafulvene derivatives were optimized at the B3LYP/6-311G** level of theory. The aromaticity indices REC (ring energy content), Schleyer's NICS, 3 He NMR chemical shift and anisotropy of magnetic susceptibility and the geometry based descriptor HOMA were used to estimate the extent of cyclic p-electron delocalization due to the substituent effect. A dramatic variation of these indices was found for electron-accepting substituents indicating great sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…The model has been successfully applied to the description of cyclic π-delocalization in a variety of carbo- 70,88-91 and heterocyclic systems, ,,, benzenoid hydrocarbons ,, and their aza derivatives, nonbenzenoid nonalternant hydrocarbons and their heteroanalogues, , spherical systems, , and Y aromatics . A great advantage of the model is that it can be used to estimate both the local and global aromaticities of a system.…”
Section: 2 Geometric Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model has been successfully applied to the description of cyclic π-delocalization in a variety of carbo- 70,88-91 and heterocyclic systems, ,,, benzenoid hydrocarbons ,, and their aza derivatives, nonbenzenoid nonalternant hydrocarbons and their heteroanalogues, , spherical systems, , and Y aromatics . A great advantage of the model is that it can be used to estimate both the local and global aromaticities of a system.…”
Section: 2 Geometric Criterionmentioning
confidence: 99%
“…Although this is attractive because no reference system is needed, in practice the anisotropy of magnetic susceptibility is difficult to apply as a measure of π-electron delocalization; its magnitude is determined by not only ring currents but other effects such as local contributions due to π-bond anisotropy and the anisotropy of CC and CH σ-bond magnetic susceptibility, as well as the anisotropy due to local paramagnetic currents . For instance, in the case of benzene about half of the anisotropy of magnetic susceptibility is attributable precisely to local contributions. ,, For these reasons, the anisotropy of magnetic susceptibility should not be considered as a fully reliable indicator of the extent of cyclic π-electron delocalization in the ring . Another suggestion is to use the nonlocal contribution to anisotropy that can be estimated by comparison of the anisotropy of magnetic susceptibility (given by eq 6) and a local contribution calculated for a model localized structure .…”
Section: 3 Magnetic Criterionmentioning
confidence: 99%
“…Even if the aromaticity indices are not equivalent, in the case of a family containing very similar structural patterns, they may inform equally well about the changes in π-electron delocalization. …”
Section: 1 Aromaticity Indices As a Measure Of π-Electron Delocalizationmentioning
confidence: 99%
“…The disputation on the statistical multidimensionality of these indices 74,77a,92 finally concluded that for a set of systems with a homogenoeus variation of the structural changes, for example, the exocyclic substituted derivatives of fulvene 93 and heptafulvene 94 or five-member heterocycles with one heteroatom, there exist very good mutual dependences among the geometric, energetic, and magnetic indices of aromaticity. However if the perturbations become less homogeneous, for example disubstituted fulvenes 93 and heptafulvenes, where noncoplanarity of sterically interacting substituents create nonhomogeneity of the substituent effect, the mutual interrelations are much worse. If the inhomogeneity is still greater, the collinearity among various aromaticity indices disappears.…”
Section: Measuring π-Electron Delocalizationmentioning
confidence: 99%
“…The older measures, the magnetic susceptibility exaltation and anisotropy of magnetic susceptibility, which have long been used, 88a-c have recently received substantial support. ,76a,78a,, However, again the magnetic susceptibility exaltation describes the whole molecule and depends on the reference system chosen. Magnetic susceptibility anisotropy is less reliable. , The local measure of π-electron delocalization, NICS, sometimes overestimates the delocalization and is criticized for its purely theoretical nature 76a. It is important to note that the original form of NICS has recently been modified: NICS(1) 90 where estimation of the shielding is at 1 Å above the plane of the center of the ring and NICS(1) zz 91 where only the perpendicular component of the tensor is used.…”
Section: Measuring π-Electron Delocalizationmentioning
confidence: 99%